Moderasi Beragama sebagai Upaya pencegahan Radikaliasme di kalangan pelajar - Bayu Saputra; Ahmad Syafiq (AL-Ikhtiar : Jurnal Studi Islam, 2024)
Religious moderation is a crucial approach in preventing radicalism among students. This approach emphasizes the importance of adopting a moderate attitude in religious practices, respecting differences in beliefs, and promoting tolerance among various interpretations of religion. Through this strategy, students are invited to understand universal religious values ​​such as peace, respecting diversity, and rejecting violence as a way to strengthen religious teachings. By encouraging religious moderation, schools and communities can create an inclusive environment where students learn to live religious lives in a balanced and harmonious manner, while still respecting their personal identities and beliefs. Abstrak Moderasi beragama adalah pendekatan krusial dalam upaya mencegah radikalisme di kalangan Pelajar. Pendekatan ini menekankan pentingnya mengadopsi sikap moderat dalam praktik keagamaan, menghormati perbedaan keyakinan, serta mempromosikan toleransi di antara berbagai interpretasi agama. Melalui strategi ini, siswa diajak untuk memahami nilai-nilai universal keagamaan seperti perdamaian, menghargai keragaman, dan menolak kekerasan sebagai cara untuk memperkuat ajaran agama. Dengan mendorong moderasi beragama, sekolah dan masyarakat dapat menciptakan lingkungan inklusif di mana siswa belajar untuk menjalani kehidupan beragama secara seimbang dan harmonis, sambil tetap menghormati identitas dan keyakinan pribadi mereka.